Evaluation of Microleakage Caused by Different LED Light Sources in Composite Resins with AutoCAD Program - Cangul, Suzan; Atas, Osman; Adiguzel, Ozkan; Erpacal, Begum; Bakir, Metin; Eskibaglar, Mehmet (Sci Printers & Publ Inc, 2020)
OBJECTIVE: To use AutoCAD software to examine the microleakage of bulk-fill composites occurring as a result of polymerization with different light sources. STUDY DESIGN: In a total of 40 extracted first molar teeth, class I cavities were opened. Then 4 groups were formed of 10 samples in each group. All the samples were restored with SDR bulk-fill composite. The samples were polymerized with an LED light source as follows: Group 1, Mikado; Group 2, Woodpecker; Group 3, Planmeca; and Group 4, CarboLED. Each tooth was divided into 2 sections. Each section was examined under stereomicroscope, and the dimensions of the leakage surface area were measured with AutoCAD software. In the statistical evaluations of the data, the Kruskal-Wallis and Tukey B tests were used. RESULTS: Significant differences were found between the groups in the statistical evaluations (p <0.05). The highest value was found in the CarboLED group and the lowest value was found in the group where Mikado light source was used. CONCLUSION: There are many factors affecting polymerization. Since there are insufficient studies on this subject, it should be supported with new research.
Keywords: AutoCAD; bulkfill composite; micro-leakage; stereomicroscope